(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2007)
In this work the possibility of malachite reduction under the combustion mode was studied using solid combined reducers of C–N–O–H type. Combustion and structure formation laws were revealed depending on different factors. It was established that controlling the conditions of reduction process it is possible to obtain copper with porosity up to 90%.